Nasal sill reconstruction with the Abbe flap after skin cancer resection: A case report - Fernanda Ramos Marcante, Renata; Daronch, Oona Tomiê; Secanho, Murilo Sgarbi; Silva, Maria Madalena (Elsevier, 2023)
Local flaps are widely known as the best option for partial nasal reconstructions depending on donor tissue laxity, vascularization, and defect shape and size. The nasolabial flap is used more often in the nasal sill. For larger defects, greater tissue mobilization with larger scars or free flaps is required. Historically, the Abbe flap has been used for lip reconstruction in patients with cleft lip deformities. It allows less retraction than other local flaps or skin grafts in patients with large defect sizes and great defect depths. This study reported on the application of the Abbe flap for nasal sill reconstruction on a 71-year-old female patient with nasal sill basal cell carcinoma who had undergone resection surgery with a posterior lip switch operation with satisfactory results. The application of the Abbe flap could be considered in patients with multiple previous surgeries and at risk for necrosis.
Keywords: Basal cell; Myocutaneous flap; Nasal defects; Nasal diseases; Neoplasms; Nose; Surgical flaps